The use of copper-based antifoulings on aluminium ship hulls. (15th November 2015) - Bagley, Frank; Atlar, Mehmet; Charles, Alasdair; Anderson, Colin
Abstract: Copper, most commonly in the form of copper oxide, is used in the majority of marine antifoulings globally, but some paint companies do not allow their copper oxide based antifoulings to be used on aluminium hulls. This is because aluminium is more anodic in the electrochemical series than copper and if the two are in direct connect in sea water, the aluminium will corrode away. This galvanic reaction only occurs if copper metal is in direct contact with aluminium, and since modern copper oxide based antifoulings contain virtually no metallic copper there appears to be no valid reason for the ultra-cautious approach regarding the use of copper oxide based antifoulings on aluminium hulls. A number of different copper-based commercial antifoulings were applied on suitably prepared Marine-grade aluminium panels, along with an un-coated control panel. The panels were immersed in seawater. Furthermore a laboratory experiment was also undertaken where coated aluminium panels were submerged in a salt water solution as a controlled experiment. All the samples were then analysed using electron microscopy. Copper leaching out of copper oxide based antifoulings had no effect on the corrosion of Marine-grade aluminium. Highlights: The antifouling coatings tested performed very differently depending on their permeability. The corrosion that is present on the samples, is of a localised nature and formed at the edge of the coating, where differing amounts of oxygen created an oxygen differential accelerating the corrosion. Copper oxide leaching out of copper based antifoulings had no effect on the corrosion of Marine-grade aluminium.